Baghdad Music Journal. - THOMPSON IV, WILLIAM A.; ALBERT, JEFFREY (Leonardo Music Journal, 2015)
The author was deployed to Iraq as a member of the U.S. Army National Guard in April 2004. He left his acoustic piano roots and embraced electronic music as a way to stay involved with music during his deployment. While deployed in Iraq, Thompson recorded and released a CD entitled Baghdad Music Journal (BMJ). The soldier's recording was made and released while he was deployed to an active war zone and is a document of his experience. Describing his time in Iraq, he discusses how it has changed his musical practice.